Analisis Morfologi dan Distribusi Bakteri Fermentatif pada Bekasam Ikan Nila Melalui Pewarnaan Gram, Kristal Violet dan Safranin - Sabnatun Nikmah; Ardi Mustakim (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Bekasam is a traditional fermented product made from tilapia (Oreochromis niloticus) containing a variety of fermentative microorganisms. This study aims to observe the morphology and distribution of fermentative bacteria in bekasam tilapia using the Gram staining method with crystal violet and safranin. Bekasam samples were fermented traditionally, then 1 gram of sample was taken and serial dilutions were carried out, followed by cultivation on Nutrient Agar (NA) media. The growing colonies were stained using crystal violet, iodine, alcohol, and safranin. This differential staining allows the identification of Gram-positive (purple) and Gram-negative (pink) bacteria. Microscopic observations showed a variety of bacterial shapes, including rod-shaped (bacilli) and spherical (cocci), with a fairly even distribution of Gram-positive and negative bacteria. The conclusion of this study is that bekasam contains a mixture of fermentative bacteria that can be identified through Gram staining, and this method is effective for the initial characterization of microorganisms in fermented foods. This research is useful for supporting the development of safer and more functionally valuable traditional fermented products. Furthermore, the results of this study also demonstrate the importance of understanding the role of fermentative bacteria in the bekasam-making process, which can contribute to the quality and safety of fermented products. By understanding the types and distribution of bacteria involved, producers can better understand the factors that influence the fermentation process, such as temperature, time, and raw materials. This knowledge also opens up opportunities to improve bekasam quality, both in terms of taste, texture, and nutritional content. Therefore, further research into the characteristics of other microorganisms involved in bekasam fermentation is crucial to ensure that this product is not only safe for consumption but also offers greater health benefits for consumers.